Percepção de justiça e desonestidade acadêmica: um estudo com estudantes do curso de ciências contábeis - Débora Santos (2019)
Academic dishonesty is not a recently faced issue by the Teaching Institutions, it is so recurring and old that has expanded to other environments, like the professional. Specifically related to the Accounting Sciences students, it is crucial that already at the academic environment, their behavior should be guided by honesty and ethics, once there is no questionings about the integrity of their deeds and actions as active individuals in the labor market. The environment in which accounting professional act and even the essence of the developed activities, has been requiring a high standard of honesty, so that a reliable relationship between the professional and the claimants of their services should exist. It is in the course of the academic life that the students will learn about the occupation technique, besides developing skills that will gather and enrich their professional practices. During that phase, the professors image might be the first reference to the student about a fair and upright professional, that image can guide them to the preservation of ethics and honesty extension to the professional practice. Therefore, a healthy relationship between professor and student, besides a perception of being at an environment where the rules are clear, with consistent standard for grades distribution and where the evaluation procedures are equal, can reinforce in the student the importance of avoiding unsuitable behaviors, given that the perception of justice in the academic environment might be a fomenter of academic dishonest behaviors. Having that theoretical framework as basis, the main purpose of this study was to analyze the existing relationship among perception of justice in the academic environment and aspects related to academic dishonesty of Accountig Sciences graduation students. The study sample was composed by 451 survey method respondents. The findings of the research have shown that the three dimensions of academic justice have presented statistical significance, exerting influence over the academic dishonesty. When the students perceive distributive justice, procedural and interactional, they tend, on average, to practice dishonest attitudes. Related to the regulation variables, it can be observed that the student performance and the university ranking exerts influence over the academic dishonesty dependent variable, inferring that students with lower performance presents higher levels of academic dishonesty and, for being enrolled in one of the top five ranked universities on QS Latin America University Ranking 2018, they present a higher tendency to get involved with academic cheating. The variables age and time of university were also statistically significant, being related with academic dishonesty.